Формування креативного стилю мислення в структурі когнітивного розвитку особистості - Давидов, П. Г.; Ромашка, С. В.; Ромашка, О. О. (НТУ "ХПІ", 2015)
Розкривається сутність пізнавально-креативного феномену та шлях і засоби його розвитку у професійній діяльності майбутнього спеціаліста. Аналізуються концепції вивчення психолого-педагогічних умов пізнавально- креативного мислення студентства та професіоналів, зокрема, теорії розв’язання винахідницьких завдань (ТРВЗ). Розглядається роль індивідуальних навчально-дослідних завдань (ІНДЗ) та науково-дослідної роботи студентів (НДРС) у формуванні критичного мислення та пізнавально - наукової творчості.

The essence of the concept creativity and the ways of its development in the professional activity of the would-be specialist are analyzed. The conceptions of studying of psychological-pedagogical conditions of the creative thinking of the students and professionals are analyzed, in particular, the theory of solution of the inventive tasks (TSIT). The role of the individual teaching-researching tasks (ITRT) and scientificresearching students’ work (SRSW) in the formation of creative thinking and cognitine- scientific creativity .
Formation of creative style of thinking in the structure of the cognitive development of the individual
Keywords: пізнання; творчість; педагогічні умови; наукове мислення; cognitivity; creativy; persone; pedagogy conditions; scientific thincing